(untitled) (Existential Analysis: Journal of the Society for Existential Analysis, 2008)
This paper introduces the work of two Canadian writers and psychologists, Nedra Lander and Danielle Nahon, as expressed in their 2005 text, The Integrity Model of Existential Psychotherapy in Working with the ‘Difficult Patient’. The Integrity model is based on an existential approach to living and views psychological difficulties as originating from a lack of fidelity to one’s values. The authors, in conversation (or trialogue as they quickly came to refer to the process), explore how their approach to psychotherapy can enhance other therapeutic models or stands on its own to offer a valuable alternative perspective on the causes of psychological distress. Possible limitations of the model and future development it may undergo are also discussed.